Contours of Indo-US Strategic Relations and Dilemma of Chinese Containment - Mujahid Hussain, Tauqeer Hussain Sargana (JSSH, 2023)
The end of Cold War has given impetus to a transformed international order vested with economic orientation. Though, the US emerged as the sole super power so does nations like China, India, South Africa, Japan, and Brazil announced their bid to form multi-polar order. This bipartisanship of the evolving order orchestrated new power corridors that created both intellectual and physical domains for progressive and ambitious nations to fill the gap. Concepts like end of history, clash of civilization, and Jihad vs. McWorld took the most of political posturing. On the one side intellectuals were trying to frame a world suitable to the already envisioned ‘new world order’ analogy and on the other hand few states were charging the global environment on economic fronts. This gave rise to an amalgamation of politics with economics and paved the way for a greater and stable political system. It also marked beginning of positively transformed relations between India and the United States when the former entered into liberal international order propagated by the then US President George W. Bush. Today, the kind of relations both nations cherish has been established on the so-called plea that ‘the two largest democracies (D2) have potential to develop the most crucial strategic alliance in the coming decades that would inevitably help them to shape the existing world order towards a more balanced and politically viable for the two strategic allies’. This research calls the Indo-US plea a ‘D2 Strategy’. The study concludes that the nature of bilateral relations between India and United States are multifaceted, whereas the containment of China is the bed-rock element behind their strategic partnership. The study has applied inductive method with that of ‘Analytical Eclecticism’ approach to evaluate the so-called strategic relations of the two biggest democracies.